Left Ventricular Outflow Tract Obstruction Following Mitral Valve Replacement: Challenges for Transcatheter Mitral Valve Therapy. Issue 5 (3rd September 2018) - Asgar, Anita W.; Ducharme, Anique; Messas, Nathan; Basmadjian, Arsene; Bouchard, Denis; Pellerin, Michel
ABSTRACT: In the race to develop a transcatheter mitral valve, experience with new techniques and devices has resulted in revisiting a previously known complication of surgical mitral valve replacement and repair: left ventricular outflow tract obstruction. This entity, first described in 1977, is dynamic in nature in many cases and multifactorial. The ability to appropriately predict and treat this complication rests on a thorough understanding of the pathophysiology and anatomical considerations. This review will review the pathophysiology of left ventricular outflow obstruction, discuss important pre-procedure imaging, procedural evaluation of obstruction, and therapeutic options.